PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN YPP DARUL HUDA WONODADI BLITAR - Nurul Huda (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
This study aims to analyze the influence of leadership style and organizational culture on employee job satisfaction. The hypothesis is proposed: the style of leadership has a significant influence on employee job satisfaction, culture organization has a significant influence on employee job satisfaction and leadership style and organization culture simultaneously has a significant influence on employee job satisfaction. The sampling method used in this study is probability proportional to size (PPS) where the number of samples is taken proportionately from existing departements. By using the Solvin formula approach with a tolerable sampling error percentage of 5% then the total of samples was determined by as many as 91 people spread in all existing departements of 118 total workers. These result study, can be concluded by some conclusions there are leadership style has not significant influence on job satisfaction. organizational culture significantly influence on job satifaction. leadership style and organizational culture simultaneously have a significant influence on job satisfaction.